A Glimpse on Paradi Guna and its Application in Ayurveda Chikitsa & Anusandhan - A Conceptual Study - Jadhav, Komal M; Vyshnavi , R; Ajith , Krishnan M (International Research Journal of Ayurveda & Yoga, 2023)
Ayurveda is the ancient life science, which aims at maintenance of health and elimination of diseases. One can find reference to various basic principles in Ayurveda. Guna siddhanta is one such basic principle explained by our acharyas. Various classifications of guna(characteristic feature) & its utility in chikitsa(treatment) are mentioned in Ayurveda Texts. Guna (characteristic feature) is one of the prime factors considered in Ayurveda. It means characteristic feature. Paradi gunas are also called as chikitsakiya guna as they are useful in treating the patients. It includes Para, Apara, Yukti etc. Research is classified into basic and applied. Basic research includes finding new things by using fundamental principles. For Ayurveda Scholars there is much need of application of these fundamental principles in Chikitsa (treatment) as well as in anusandhan(research). This article aims on application of paradi gunas in